ZEMCH Research Initiatives: Mass Customisation and Sustainability (MDPI - Multidisciplinary Digital Publishing Institute, 2015)
The earth is experiencing the adverse effect of climate change. In response to growing global warming issues and the constant increase of energy prices, house-builders and housing manufacturers today are becoming more responsive to the delivery of net zero energy and carbon dioxide emission sustainable homes than ever. Within this context, the sustainability may embrace housing economy and adequacy beyond the legitimacy in which the quality barely coincides with individuals' dynamic various needs, desires and expectations. In this special issue, 'mass customisation' is reviewed being considered as a paradoxical concept which has been recognised as a means to lessen production costs of end-user products whilst achieving the customisability through economies of scope rather than economies of scale. Nevertheless, the housing industry's business operation tends to follow routines and the close system mode of operation often hinders the enterprises from adopting unfamiliar inn ovations which may be inevitable in realising the delivery and operation of socially, economically and environmentally sustainable homes. In order to deliver a marketable and replicable zero energy/emission mass custom home, or ZEMCH, the strategic balance between the optional and standard features seems to be critical. The optional features may be provided with the aim to enhance design quality (or customizability) that helps contribute to satisfying desires and expectations of individual stakeholders. The standard equipment, on the other hand, needs to be installed in buildings as it aims to exceed product quality whose levels can be adjusted in conjunction with societal demands and requirements. This edition encompasses a wide spectrum of hopes and fears around the design, production and marketing approaches to the ZEMCH delivery and operation, and showcases some exemplars budding out in different climates around the globe